Aktivitas Penghambatan Enzim α-Glukosidase Senyawa β-Sitosterol dari Fraksi Etil Asetat Daun Salam [Syzygium polyanthum (Wight.) Walp - Sulastri, Lilik; Zulfadhli, Muhammad; Alwie, Rakhmat Ramdhani; Ramani, Sofyan; Prasetiyo, Andri; Simanjuntak, Vino Soaduon (Jurnal Fitofarmaka Indonesia, 2024)
Diabetes mellitus, also known as diabetes, is an endocrine disease characterized by sustained high blood sugar levels. Diabetes is caused by the pancreas not producing enough insulin, or the body's cells becoming unresponsive to the effects of the hormone. Common symptoms include thirst, polyuria, weight loss, and blurred vision. If left untreated, the disease can lead to various health complications, such as disorders of the cardiovascular system, eyes, kidneys, and nerves. In general, the treatment of diabetes mellitus is done with insulin therapy and various synthetic drugs, but these treatments have side effects. Another alternative is treatment using herbs, including salam leaves (Syzygium polyanthum (Wight.) Walp) which can be used as an inhibitor for the α-glucosidase enzyme. This study aims to isolate and determine the levels of β-sitosterol from the ethyl acetate fraction of salam leaves which have α-glucosidase enzyme inhibitory activity. Extraction was carried out by maceration using 96% ethanol, then partitioned with ethyl acetate and water (1:1). The ethyl acetate fraction was tested for the inhibitory activity of the α-glucosidase enzyme, then isolated by column chromatography method (SiO2; i.n-hexane-ethylacetate = 10 : 1 ~ 1 : 1, ethylacetate; ii.n-hexane-ethylacetate = 5 : 1 guided by testing enzyme inhibitory activity until pure isolates were obtained. The isolates were identified by spectrophotometry (IR) compared with the standard β-sitosterol compound. The results showed that isolates F.4-5 was a β-sitosterol compound with a concentration of 177.13 mg/g extract and had α-glukosidase enzyme inhibitory activity with an IC50 of 93.7 μg/mL.